1997
DOI: 10.1111/j.1440-1827.1997.tb04488.x
|View full text |Cite
|
Sign up to set email alerts
|

Nemaline bodies of skeletal muscle fibers of the neck in a case of pharyngeal cancer

Abstract: Nemaline bodies were found in the regenerating muscle fibers of the neck of a 74-year-old Japanese male with pharyngeal cancer. Histologically, the nemaline bodies were needle-shaped structures and hematoxophilic with phosphotungstic acid-hematoxylin stain. Electron microscopic examination suggested that they arise as extensions of the Z bands. Although nemaline bodies occur in a variety of pathological conditions other than nemaline myopathy, their occurrence in regenerating skeletal muscle fibers invaded by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Indeed, nemaline bodies can be found in several neuromuscular disorders other than nemaline myopathy. 13,14 Whether or not nemaline rods diminished in our patient with treatment is not known, as a muscle biopsy was not performed after clinical improvement. In nemaline myopathy, an increase of alpha-actinin has been reported in patients with mutations in the muscle alphaskeletal actin gene (ACTA1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, nemaline bodies can be found in several neuromuscular disorders other than nemaline myopathy. 13,14 Whether or not nemaline rods diminished in our patient with treatment is not known, as a muscle biopsy was not performed after clinical improvement. In nemaline myopathy, an increase of alpha-actinin has been reported in patients with mutations in the muscle alphaskeletal actin gene (ACTA1).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of nemaline bodies at a stage when clinical symptoms were already apparent and the muscle biopsy showed myopathic changes may indicate that they occur secondarily in the course of disease. Indeed, nemaline bodies can be found in several neuromuscular disorders other than nemaline myopathy . Whether or not nemaline rods diminished in our patient with treatment is not known, as a muscle biopsy was not performed after clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that NB per se is not specific although its presence is a mandatory finding of nemaline myopathies. NB can be observed also in idiopathic inflammatory myopathies, alcoholic myopathy, advanced stage of muscular dystrophies, hypothyroidism, cancer invasion, and chronic neuropathy like spinal muscular atrophy [37][38][39][40][41][42]. Empirically, a small number of fibers with NB can be seen physiologically if the muscle is biopsied near tendon.…”
Section: Muscle Pathologymentioning
confidence: 99%
“…However, there has also been a case of nemaline rod myopathy reported by Zamecnik 9 after radiation treatment without chemotherapy for laryngeal squamous cell carcinoma. Interestingly, Kimura et al 6 reported nemaline bodies in muscle after chemotherapy treatment alone of pharyngeal cancer. Kimura suggested that an alteration of myotu-bules and small nerves by infiltrating neoplastic cells may cause a reactive inflammatory process.…”
Section: Several Reportsmentioning
confidence: 99%